Conscious and nonconscious memory effects are temporally dissociable - Slotnick, Scott D. (2010)
Intentional (explicit) retrieval can reactivate sensory cortex, which is widely assumed to reflect conscious processing. In the present study, we used an explicit visual memory event-related potential paradigm to investigate whether such retrieval related sensory activity could be separated into conscious and nonconscious components. During study, abstract shapes were presented in the left or right visual field. During test, old and new shapes were presented centrally and participants classified each shape as “old-left”, “old-right”, or “new”. Conscious activity was isolated by comparing accurate memory for shape and location (old-hits) with forgotten shapes (old-misses), and nonconscious activity was isolated by comparing old-left-misses with old-right-misses and vice versa. Conscious visual sensory activity had a late temporal onset (after 800 ms) while nonconscious visual sensory activity had an early temporal onset (before 800 ms). These results suggest explicit memory related sensory activity reflects both conscious and nonconscious processes that are temporally dissociable.